The Influence of Managerial Ownership Structures, Leverage, Financial Distress and Corporate Social Responsibility on Accounting Conservatism - Dwiyan Teguh Nugraha Ginting; Giant Adi Yuniarta; Ni Kadek Sinarwati (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze the effect of managerial ownership structure, leverage, financial distress, and corporate social responsibility (CSR) on accounting conservatism in companies listed on the Indonesia Stock Exchange (IDX) for the period 2022-2022. Accounting conservatism is measured by an approach that prioritizes fairness of reporting that is more careful in recognizing revenue and expenses. Managerial ownership structure is expected to influence conservative accounting decision-making, while leverage and financial distress are assumed to encourage companies to be more careful in reporting their financial performance. In addition, CSR is considered a variable that can improve the company's image and influence more conservative accounting decisions. The method used is multiple regression analysis with secondary data processing from the annual reports of listed companies. The results of the study indicate that managerial ownership structure and leverage have a significant effect on accounting conservatism, while financial distress and CSR do not have a significant effect. These findings provide an important contribution to understanding the influence of internal company factors on more careful accounting practices, as well as providing implications for regulators and policy makers in formulating more appropriate accounting policies to improve transparency and reliability of financial statements.